Parasites of the neotropic cormorant nannopterum (Phalacrocorax) brasilianus (aves, phalacrocoracidae) in Chile - González Acuña, Daniel (2020)
The Neotropic cormorant Nannopterum (Phalacrocorax) brasilianus (Suliformes: Phalacrocoracidae) is widely distributed in Central and South America. In Chile, information about parasites for this species is limited to helminths and nematodes, and little is known about other parasite groups. This study documents the parasitic fauna present in 80 Neotropic cormorants’ carcasses collected from 2001 to 2008 in Antofagasta, Biobío, and Ñuble regions. Birds were externally inspected for ectoparasites and necropsies were performed to examine digestive and respiratory organs in search of endoparasites. Ectoparasites collected were cleared and mounted for identification under a microscope. Fecal samples were also evaluated to determine the presence of protozoan parasites employing a flotation technique. A total of 44 (42.5%) of birds were infested with at least one ectoparasite species, while 77 (96.25%) were carrying endoparasites. No protozoan forms were found after examination. Most prevalent endoparasite species found were Contracaecum rudolphii s. l. (72/80, 90%), followed by Pectinopygus gyroceras (33/80, 41.25%), and Profilicollis altmani (26/80, 32.5%). This is the first report of P. altmani, Baruscapillaria carbonis, Avioserpens sp., Cyathostoma (Cyathostoma) phenisci, and Eidmaniella pelucida in the Neotropic cormorant. These findings also expand the distributional range of Andracantha phalacrocoracis, Paradilepis caballeroi, Hysteromorpha triloba, and P. gyroceras to Chile.